Effect of verbal instructions on muscle activity and risk of injury to the anterior cruciate ligament during landing - Cowling, E. J.; Steele, J. R.; McNair, P. J. (British Journal of Sports Medicine, 2003)
Background: Minimising the likelihood of injury to the anterior cruciate ligament (ACL) during abrupt deceleration requires proper synchrony of the quadriceps and hamstring muscles. However, it is not known whether simple verbal instructions can alter landing muscle activity to protect the knee.